Poly[bis(mu(3)-thiocyanato-kappa N-3:S:S `)(mu(2)-thiocyanato-kappa N-2/S)(4 `-p-tolyl-2,2 `/6 `,2 `'-terpyridine-kappa N-3,N `,N `')cadmium(II)silver(I)] - Li, Yu-Yang; Wei, Zhen-Hong; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, [AgCd(NCS)(3)(C22H17N3)](n), is a heteroatom ribbon coordination polymer. The central Cd atom is chelated by the 4'-p-tolyl-2,2':6',2-'' terpyridine ligand and is coordinated by the N atoms of three thiocyanate ions in an octahedral geometry whereas the Ag atom is coordinated by the four S atoms of four thiocyanate ions in a distorted tetrahedral geometry. Of the three thiocyanate ions, one functions in a mu 2-bridging mode and two in a mu 3-bridging mode. The ribbon coordination polymer propagates along the a-axis.